2022
DOI: 10.4149/neo_2021_210805n1113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions of MHC class I antigen processing and presentation pathway to bladder cancer risk and recurrence

Abstract: Human leukocyte antigen class I (HLA class I) antigen processing and presentation pathway (APP) defines anticontrol HLA class I expression in the tumor and the repertoire of presented tumor antigens. At the same time, vascular endothelial growth factor (VEGF) acts as an immunomodulator in the tumor microenvironment. The objective of the current study was to examine the association of single nucleotide polymorphisms (SNPs) in the ERAP1, ERAP2, TAP1, TAP2, TAPBP, IFNG genes with the corresponding mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Additionally, our observation of elevated macrophages in OS was consistent with previous studies (39). Similarly, using RNA-seq data, we found that a lower expression of APM-related genes, including B2M, CIITA, ERAP2, TAP2 and TAPBPL, was also associated with a shorter PFS, reflecting the increasing interest in APM biomarkers for clinical outcome and immune escape in cancer (40). Finally, RNA-seq data revealed a pattern whereby a decreased allele-specific HLA-C expression, combined with high NK cell infiltration, was linked with improved PFS.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, our observation of elevated macrophages in OS was consistent with previous studies (39). Similarly, using RNA-seq data, we found that a lower expression of APM-related genes, including B2M, CIITA, ERAP2, TAP2 and TAPBPL, was also associated with a shorter PFS, reflecting the increasing interest in APM biomarkers for clinical outcome and immune escape in cancer (40). Finally, RNA-seq data revealed a pattern whereby a decreased allele-specific HLA-C expression, combined with high NK cell infiltration, was linked with improved PFS.…”
Section: Discussionsupporting
confidence: 91%
“…As for tapasin ( TAPBP ), it constitutes an integral component of the peptide-loading complex that allows HLA-I to present antigens on the cell surface [ 40 ]. While a reduction in TAPBP expression has been associated to tumor progression in colorectal cancer and chronic hepatitis B [ 41 , 42 ], the rs2071888 SNP has been associated with wild type gastrointestinal tumors and gallbladder cancer [ 43 , 44 ]. Furthermore, asthmatic patients carrying the CG and GG genotypes may have a higher decline in forced expiratory volume in 1 s after aspirin provocation when compared to those patients carrying the GG genotype [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that mutations or changes in the expression of TAP1 play roles in tumor immune escape and affect tumor progression, while still remain certain controversial (12)(13)(14)(15)(16)) in terms of cancer. A considerable amount of research has focused on the relationship between polymorphisms in TAP1 and tumorigenesis development (17)(18)(19).On the one hand, in some cancers, such as colorectal cancers, researchers work to promote antigen presentation and thereby enhance tumor sensitivity to drugs (20)(21)(22). The high expression of TAP1 may be associated with the production of more tumor neoantigens, which in turn initiate tumor immunity (23).…”
Section: Introductionmentioning
confidence: 99%